English Teachers’ Investigation Of Windows Movie Maker As Technology In Teaching Speaking - Ika Wulandari (Universitas Muhammadiyah Surabaya, 2019)
Because of the widespread use of computers, most professions have been influenced by them in one way or another (Gough-Jones, 1995). Teachers need to be more creative in integrating technology into the classroom, especially in teaching speaking which is considered as the most challenging skill for students to learn. Thus, the aims of this study are to introduce Windows Movie Maker (WMM) as a technology in teaching speaking and to reveal the attitudes of ten English teachers towards its utilization. The implementation of WMM is illustrated through sample activities. Besides, to collect data regarding their attitudes, the participants were directly distributed a document consists of an introduction to this tool, tutorials on how to apply it, and sample of WMM slides. They were then asked to write their reflections on WMM application and kind of activities they could use in teaching speaking. The collected qualitative data was analyzed by means of content analysis. It was revealed that the participants mostly gave positive attitudes towards the use of WMM and they also shared their ideas about teaching activities incorporating this tool. In sum, the use of new technology in teaching speaking is likely to lead to a more effective ELT process. Â Keywords: Technology in ELT, Windows Movie Maker, Teaching Speaking.